Financial Empowerment for Women: Closing the Gender Wealth Gap - Agusti, Anatia; Edriani, Devi; Ilyas, Andre (Equator Journal of Management and Entrepreneurship (EJME), 2024)
This research investigates the role of financial literacy, access to financial resources, and financial empowerment in addressing the gender wealth gap within PT. Bank Rakyat Indonesia (Persero). Using a quantitative research design and employing the Smart PLS analysis tool, the study examines the direct and indirect effects of these variables on the gender wealth gap based on data collected from 100 bank customers. The findings reveal significant direct effects of financial literacy and access to financial resources on financial empowerment, which subsequently influences the gender wealth gap. Additionally, significant indirect effects of both financial literacy and access to financial resources on the gender wealth gap through financial empowerment are observed. These results underscore the importance of implementing comprehensive strategies to enhance financial literacy, improve access to financial resources, and foster empowerment among women within the organization. Addressing these factors is crucial for promoting financial inclusion, narrowing the wealth disparity, and advancing gender equity in wealth accumulation at PT. Bank Rakyat Indonesia (Persero).